Optimization of structure parameter of linear oscillatory actuator for high thrust characteristics and mobility performance - Abdul Shukor , Fairul Azhar; Misron, Norhisam; Khamis, Alias; Raja Othman, Raja Nor Firdaus Kashfi; Nirei, Masami; Wakiwaka, Hiroyuki (2010)
This paper discuss on optimization of structure parameters of LOA in order to develop high thrust and light weight of LOA. The structure parameters are including the taper parameter as well as size of permanent magnet and coil. There are two method use toward the optimization process which are finite element method (FEM) and permeance analysis method (PAM). As a result, a high thrust of LOA with starter thrust of 230 N and light weight about 2.1 kg has been fabricated.